2019
DOI: 10.1534/genetics.118.301893
|View full text |Cite
|
Sign up to set email alerts
|

Maximum Likelihood Estimation of Fitness Components in Experimental Evolution

Abstract: Estimating fitness differences between allelic variants is a central goal of experimental evolution. Current methods for inferring such differences from allele frequency time series typically assume that the effects of selection can be described by a fixed selection coefficient. However, fitness is an aggregate of several components including mating success, fecundity, and viability. Distinguishing between these components could be critical in many scenarios. Here, we develop a flexible maximum likelihood fram… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 43 publications
2
38
0
Order By: Relevance
“…It remains unclear how D. willistoni males (and males of other species without sex combs) are able to efficiently grasp females prior to copulation (Video 16). However, differences in females might be part of the answer, as D. melanogaster y 1 mutant males are able to mate with y 1 mutant females at rates similar to wild-type males (Bastock, 1956; Dow, 1976; Heisler, 1984; Liu et al, 2019; Figure 4—figure supplement 3A, FET, p=1). That said, removing all melanin from D. melanogaster sex combs by knocking down Laccase-2 reduced mating efficiency with y 1 females (Figure 4—figure supplement 3B, FET, p=0.02 and 0.0001), suggesting that the brown melanin remaining in y 1 sex-combs (Figure 4B) played a role in the mating success of y 1 males with y 1 females.…”
Section: Resultsmentioning
confidence: 99%
“…It remains unclear how D. willistoni males (and males of other species without sex combs) are able to efficiently grasp females prior to copulation (Video 16). However, differences in females might be part of the answer, as D. melanogaster y 1 mutant males are able to mate with y 1 mutant females at rates similar to wild-type males (Bastock, 1956; Dow, 1976; Heisler, 1984; Liu et al, 2019; Figure 4—figure supplement 3A, FET, p=1). That said, removing all melanin from D. melanogaster sex combs by knocking down Laccase-2 reduced mating efficiency with y 1 females (Figure 4—figure supplement 3B, FET, p=0.02 and 0.0001), suggesting that the brown melanin remaining in y 1 sex-combs (Figure 4B) played a role in the mating success of y 1 males with y 1 females.…”
Section: Resultsmentioning
confidence: 99%
“…Loss of female mate preference may have significant evolutionary consequences, as females across a variety of taxa have been shown to choose male traits that confer fitness benefits [43, 44, 45, 46]. The consequence of the loss in female preference for red color observed in this study is uncertain, however, there is evidence from other studies that the preference for red coloration may provide important benefits.…”
Section: Discussionmentioning
confidence: 79%
“…To reveal the phylogenetic position of 'Emily Bruner' with these members, a phylogenetic analysis was performed based on 10 complete cp genomes, and one taxa from Helwingia was served as outgroup. The neighbor-joining (bootstrap repeat is 10,000) and maximum likelihood (bootstrap repeat is 1000) were used for constructing phylogenetic trees using PhyML v3.0 (http://www.atgc-montpellier.fr/phyml/) (Liu et al 2019). The phylogenetic tree showed that 'Emily Bruner' closely related to its female parent I. cornuta species (Figure 1).…”
mentioning
confidence: 99%
“…The neighbor-joining (bootstrap repeat is 10,000) and maximum likelihood (bootstrap repeat is 1000) were used for constructing phylogenetic trees using PhyML v3.0 ( http://www.atgc-montpellier.fr/phyml/ ) (Liu et al. 2019 ). The phylogenetic tree showed that ‘Emily Bruner’ closely related to its female parent I. cornuta species ( Figure 1 ).…”
mentioning
confidence: 99%